Relacionamento professor-aluno no ensino médio : a perspectiva do aluno - Togatlian, Marco Aurélio (2011)
The relationship between teacher and student is still poorly investigated. Most part of the studies on the topic emphasizes childhood education and elementary school. Until this time in the student's school life, personal relationships are regarded as one of the main variables that contribute to their future academic success. This study aims at investigating the relationship between teacher and student in high school, gateway to the university and, therefore, for future professionals. At this stage of life, the school does not seem to prioritize the relationship between teachers and their adolescent students. The aim of this study is to investigate the role of relationship between teacher and student in high school, trying to point out the convergences between what the students consider as important for a good relationship with their teachers and how students depict the ideal teacher. A hundred and twenty students regularly enrolled in the three grades of high school in the city of Rio de Janeiro participated in the study. The data were discussed based on studies about relationships and the proposals of Robert Hinde served as a theoretical reference for organizing and interpreting data. Two identical questionnaires with forty-six questions each divided into six dimensions according to the Hinde’s proposal for the studies about relationships have been used. One of the questionnaires was about the relationship with the teacher with which the student recognized to have the best relationship, and the other was directed to the teacher with whom the student considered to have the worst relationship. This instrument was designed to investigate the perception that the student had of the two specific teachers in personal and professional terms and aspects of his/her relationship with these teachers. The students pointed out a teacher with whom they considered to have the worst relationship and a teacher with whom they considered to have the best relationship. Part of these students (100) wrote a text between fifteen and twenty fife lines about the ideal teacher. The text was written after answering to the questionnaires. The essay on "The ideal teacher" was used for qualitative data analysis. An examination of the essays was done by content analysis. At the end, convergences and divergences between the questionnaires and essays have been pointed. Both the questionnaires and the essays revealed the centrality of the relationship between teacher and student from a professional and a personal point of view.